Tolerogenic Dendritic Cells and T-Regulatory Cells at the Clinical Trials Crossroad for the Treatment of Autoimmune Disease; Emphasis on Type 1 Diabetes Therapy - Phillips, Brett Eugene; Garciafigueroa, Yesica; Engman, Carl; Trucco, Massimo; Giannoukakis, Nick (Frontiers in Immunology, 2019)
Tolerogenic dendritic cells and T-regulatory cells are two immune cell populations with the potential to prevent the onset of the clinical stage of type 1 diabetes and to manage the underlying autoimmunity beginning at the time-at-onset and onwards. Initial phase I trials demonstrated that the administration of a number of these cell populations, generated ex vivo from peripheral blood leukocytes, was safe. Outcomes of some of these trials also suggested some level of autoimmunity regulation by the increase in the numbers of regulatory cells at different points in a network of immune regulation in vivo. As these cell populations come to the cusp of pivotal phase II efficacy trials, a number of questions remain to be addressed to verify that at least one mechanism of action is operational and through this mechanism, to identify biomarkers predictive of, and to monitor efficacy in regulation of the underlying autoimmunity. At the same time, the absence of a common phenotype core among the different dendritic cell and T-regulatory cell populations that have completed phase I and early phase II trials necessitates a better understanding of what makes these cells tolerogenic, especially if a uniform phenotypic core cannot be identified. Finally, the inter-relationship of tolerogenic dendritic cells and T-regulatory cells for survival, induction, and maintenance of a tolerogenic state that manages the underlying diabetes autoimmunity raises to possibility to co-administer or even to serially-administer tolerogenic dendritic cells together with T-regulatory cells as a cellular co-therapy, enabling the best possible outcomes. This is currently a gap in knowledge that this review aims to address.